Factors affecting the welfare of a family with disabilities - Temirbayeva, D.M.; Gelashvili, N.N.; Pritvorova, T.P.; Simonov, S.G.; Sabyrzhan, A. (KU Publ., 2022)
Object: The socio-economic status of households with disabled children is the subject of worldwide attention for scientists and public policy. Such households suffer from a high probability of a social risk, which is generated by economic and social environment factors. The study aims to identify factors affecting the welfare of a family with child limitations, such as “mental retardation” and to assess the impact of each group of factors. Methods: Authors applied the method of a sociological survey in five regions of Kazakhstan. The interview used a methodological approach based on identification of four types of restrictions: Direct costs for a child, indirect household losses, assessment of the possibility for a parent to find employment and maintain their health. The survey results were processed by PLS3-PM structural modeling, for which we accepted four types of constraints as dependent variables. Findings: The econometric model allowed us to prove hypotheses regarding the degree of impact of restriction factors on the welfare of households with disabled children. To the greatest extent, the welfare of the family is li mited by direct out-of-pocket expenses on the child’s needs. A significant value is the allowances associa ted with disability as the most important source of income. Statistically, insufficient volumes of medical and special social se rvices increase direct costs considerably. An increase in the costs for a child is a prerequisite for reducing the family’s disposable income and its poverty. Conclusions: The birth of a disabled child negatively affects the employment opportunities of at least one family member, their health, and development of human capital. Besides the loss of a parent’s income, indirect losses of a family have a significant prolonged effect on its long-term wellbeing as there is no affordable system for bringing a child into independent life in Kazakhstan.
Мүмкіндіктері шектеулі отбасының әл-ауқатына әсер ететін факторлар
Факторы влияния на благосостояние семьи с ограниченными возможностями
Keywords: family with a disabled child; factors of welfare restrictions; poverty; PLS3-PM model; social transfers